2014
DOI: 10.1179/1743277414y.0000000087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cartographic Elevation Visualizations and Map-reading Tasks on Eye Movements

Abstract: Users prefer more realistic visualizations, even though they may be less efficient or even detrimental for a given task. In some previous studies, the evidence has shown that relief shading facilitates the landform interpretation while other studies have provided contrary results. In the present study, the effect of three different visualizations of elevation information on eye movements and performance was investigated in visual search, area selection, and route planning tasks. The results showed that the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…To name a few common use cases, contours are useful for rapid reading of large terrain formations, for estimating elevation differences, or for comparing elevations of distant places (e.g. Putto, Kettunen, Torniainen, Krause, & Sarjakoski, 2014;Wilkening & Fabrikant, 2011). Contours are seldom represented alone but mostly together with a multitude of other cartographic symbols, typically in topographic maps.…”
Section: Introductionmentioning
confidence: 99%
“…To name a few common use cases, contours are useful for rapid reading of large terrain formations, for estimating elevation differences, or for comparing elevations of distant places (e.g. Putto, Kettunen, Torniainen, Krause, & Sarjakoski, 2014;Wilkening & Fabrikant, 2011). Contours are seldom represented alone but mostly together with a multitude of other cartographic symbols, typically in topographic maps.…”
Section: Introductionmentioning
confidence: 99%
“…Maps that include a comprehensive representation of terrain together with a landform relief (topographic or tourist maps) have not been studied from a user perspective as deeply as other types of geovisualizations (i.e., city maps or urban plans; Burian, Šťávová 2009), although their importance remains high in many common tasks, necessitating a high-level understanding of terrain (Putto et al 2014).…”
Section: State Of the Artmentioning
confidence: 99%
“…One of the first eye-tracking studies dealing with terrain visualization was performed by Chang, Antes, Lenzen (1985), who analyzed the effect of experience on reading topographic relief maps. Putto et al (2014) performed an eye-tracking study evaluating three different terrain visualizations (contour lines, relief shading, and oblique view) in solving three types of spatial tasks (visual search, area selection, and route planning). e results showed that performance on contour line visualization and shaded relief were comparable (oblique view was the slowest).…”
Section: State Of the Artmentioning
confidence: 99%
“…Contour lines are a key features of topographic maps as they make the comprehension of terrain more easy (Wilkening & Fabrikant, 2011;Putto et al, 2014). In order to produce topographic maps more quickly, contour lines are no longer drawn by cartographers based on stereoscopic vision, and are rather automatically derived from digital terrain models (DTM).…”
Section: Introductionmentioning
confidence: 99%